Integrability assessment methodology for building integrated photovoltaics: concept and application - Gayathri Aaditya Eranki; Monto Mani (International Journal of Sustainable Energy, 2020)
The existing evaluation of Building Integrated Photovoltaic systems (BIPV), limit to the system’s electrical performance, similar to conventional PV ground-mounted systems. BIPV has to deliver on both the roles of building and PV alike while catering to the needs of the society, economically. The current paper introduces the concept of Integrability, which is an attempt towards a holistic approach in evaluating BIPV systems. Integrability Methodology for BIPV evaluation has been proposed, for urban localities, which can be adopted for various PV configurations, building typologies and climatic zones. An Integrability Index has also been devised, considering various building performance factors, to evaluate and compare the performance of BIPV structures. The methodology has been applied to a 5.25 kWp BIPV system and the index has been computed to be 0.17 (on a scale of 0–1) and the various strategies that improve the index (up to 0.56) have also been discussed.